The Relationship between Servant Leadership Style, Employee Satisfaction and Employee Commitment of Telecommunication Industry Employees in Pakistan - Haider, Ali Shams (2024)
The study explores the relationships between servant leadership, employee satisfaction, and employee commitment within the telecommunications sector of Pakistan. Despite the significance of these variables for organizational success, especially in dynamic industries like telecommunications, the interplay among them has been under-researched in the Pakistani context. The primary objective of this study is to investigate the direct and indirect effects of servant leadership on employee commitment, focusing particularly on the mediating role of employee satisfaction. The study employs a causal-comparative research design, targeting a population of approximately 1.36 million employees within Pakistan's telecom sector. Based on the Morgan sample size table, a sample of 384 participants was determined to achieve a 95% confidence level. Data were collected from 397 respondents using survey questionnaires distributed across four major telecom companies. The survey instrument measured key constructs of servant leadership, employee satisfaction, and employee commitment. A pilot study was conducted to ensure the instrument's reliability before data collection. Data was analyzed using Smart PLS software, applying a range of statistical tests, including demographic analysis, descriptive statistics, reliability testing, correlation analysis, and regression analysis, to test the study's hypotheses. The findings revealed a positive and statistically significant relationship between servant leadership and employee commitment, as well as between employee satisfaction and commitment. Furthermore, servant leadership was found to have a strong influence on employee satisfaction. Importantly, employee satisfaction served as a significant mediator in the relationship between servant leadership and employee commitment, highlighting the indirect effect of leadership on commitment. These findings offer valuable insights for organizational leadership and human resource practices in the telecom sector, emphasizing the importance of servant leadership in fostering employee satisfaction and commitment. The study concludes with recommendations for future research, suggesting the exploration of additional mediating and moderating variables and the use of mixed method approaches to gain deeper insights into these relationships.